IMPLEMENTASI MODEL COLT (TIPE STRUCTURED PROBLEM SOLVING) DAN PENGARUHNYA TERHADAP KEMAMPUAN PEMECAHAN MASALAH BAGI SISWA SMA - Sudarman Na (Akademika, 2018)
Future education requires a pattern of education that is able to prepare generations who are able to face and adapt to the global community. The challenge requires a learning model that guides students to be able to think critically and be skilled in solving problems. This study aims to describe the application of the CoLT model in the learning process and find the superiority of the CoLT learning model to the ability to solve problems and prove whether this collaborative learning model is superior and in accordance with theconditions and characteristics of students in East Kalimantan. The research method of this study was designed using quasi-experimental research methods (quasi experimental) with randomized pretest-posttest kontrol group design and survey methods to obtain qualitative data. The research subjects in this study were high school students of class XI IPS who were in Bontang, Mahulu, Kutai Kartanegara and Samarinda, each of the two classes as the experimental class and the kontrol class, so the total number was 8 classes, with a totalkontrol class of 122 respondents and experimental class 116 respondents. Research results show student response to the implementation of learning with the CoLT Model is very good, it is illustrated by the percentage of pleasure with the learning with a score of 84%, the responsibility in the excellent category is strengthened by the ability to interact with the group is also good, and the end result of the response learning achievement and performance improvement 83%. Based on the results of problem solving skills, class students who learn to use the CoLT model have higher abilities than students in the kontrol class who learn to use direct (traditional) learning models.